Digital human modeling (dhm) for computer-aided ergonomics analysis in the horticulture industry - Nugraha, MH; Widyantoro, Widyantoro; Luthfi, Ajie M; IR, Anes; Rohman, Abd; MF, Willy (Universitas Muhammadiyah Jakarta, 2023)
In Indonesia, the production of water spinach increased by 9,24% from the last year, which was reasonable because water spinach was one of the most sought-after and popular types of vegetables. The farmers have exposure risk factors of work-related musculoskeletal disorders (MSDs) owing to poor watering of plant workstations using manual methods. This journal aims to explore the application of computer-aided ergonomic analysis and digital human modeling techniques in optimizing the workstations of farmers in water spinach plantations. This paper compares ergonomic scores for body posture farmers before and after improvement. Improvement was done by replacing the manual ball valve with motor operated valve (MOV), controlled (opens and closes) by farmers’ phones. Before and after improvement, body posture farmers are converted to digital human modeling and analyzed by CATIA and RULA analysis tools. The result of this paper comparing before and after improvement results in a percentage reduction in RULA Scores of 75% from a 4 to 1 value.